EVALUATION OF HISTORIC-ARCHITECTURAL POTENTIAL IN ADMINISTRATIVE DISTRICTS OF TRANSCARPATHIAN REGION IN THE CONTEXT OF RECREATION AND TOURISM DEVELOPMENT - Славік, Роман (Human Geography Journal, 2016)
The article analyzes the recreational attractiveness of recreational areas of Transcarpathian region based on the qualitative and quantitative historic-architectural potential using fuzzy logic methodology. Systematization of recreational areas of Transcarpathia by prospects of doing cultural and historical recreation activities is done. Problematic issues of recreation sphere development in Transcarpathian region are allocated, particularly the poor state of historical and architectural monuments and it's uneven placement on the regions territory.